Ice volume estimates from ground-penetrating radar surveys, Wedel Jarlsberg Land glaciers, Svalbard - Navarro Valero, Francisco José; Martín Español, Alba; Lapazaran Izargain, Javier Jesús; Grabiec, M.; Otero García, Jaime; Vasilenko, Evgeniy; Puczko, D. (Arctic, Antarctic, and Alpine Research, 2014)
We present ground-penetrating radar (GPR)—based volume calculations, with associated error estimates, for eight glaciers on Wedel Jarlsberg Land, southwestern Spitsbergen, Svalbard, and compare them with those obtained from volume-area scaling relationships. The volume estimates are based upon GPR ice-thickness data collected during the period 2004–2013. The total area and volume of the ensemble are 502.91 ± 18.60 km2 and 91.91 ± 3.12 km3, respectively. The individual areas, volumes, and average ice thickness lie within 0.37–140.99 km2, 0.01–31.98 km3, and 28–227 m, respectively, with a maximum recorded ice thickness of 619 ± 13 m on Austre Torellbreen. To estimate the ice volume of unsurveyed tributary glaciers, we combine polynomial cross-sections with a function providing the best fit to the measured ice thickness along the center line of a collection of 22 surveyed tributaries. For the time-to-depth conversion of GPR data, we test the use of a glacierwide constant radio-wave velocity chosen on the basis of local or regional common midpoint measurements, versus the use of distinct velocities for the firn, cold ice, and temperate ice layers, concluding that the corresponding volume calculations agree with each other within their error bounds.